Diagnóstico del uso de insecticidas para el combate de Plutella xylostella en Costa Rica - Araya R, L.=700 1 Monge V, L.A.; Carazo R, E.; Cartín L, V.M.
ilus. ; 9 ref.
Keywords: BRAáICA OLERACEA CAPITATA; PLUTELLA XYLOSTELLA; INSECTICIDAS; CONTROL QUIMICO; DIAGNOSTICO; COSTA RICA